2016
DOI: 10.1142/s0218957716500196
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and Stiffness Adaptations of the Transverse Carpal Ligament Associated With Carpal Tunnel Syndrome

Abstract: The purpose of this study was to investigate the morphological and mechanical properties of the transverse carpal ligament (TCL) in patients with carpal tunnel syndrome (CTS). Thickness and stiffness of the TCL in eight female CTS patients and eight female control subjects were examined using ultrasound imaging modalities. CTS patients had a 30.9% thicker TCL than control subjects. There was no overall difference in TCL stiffness between the two groups, but the radial TCL region was significantly stiffer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Carpal tunnel syndrome (CTS) is a common complaint causing hand disability in people of working age [1][2][3]. CTS is suggested to be caused by compression of the median nerve in the carpal tunnel under the transverse carpal ligament due to thickening of the ligament or other structures surrounding the median nerve [4,5]. In the chronic condition, compression and irritation of the median nerve is followed by tingling, numbness, and pain in the innervation area of the median nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is a common complaint causing hand disability in people of working age [1][2][3]. CTS is suggested to be caused by compression of the median nerve in the carpal tunnel under the transverse carpal ligament due to thickening of the ligament or other structures surrounding the median nerve [4,5]. In the chronic condition, compression and irritation of the median nerve is followed by tingling, numbness, and pain in the innervation area of the median nerve.…”
Section: Introductionmentioning
confidence: 99%
“…The TCL may become thicker and stiffer in response to repetitive muscle-ligament interaction during thumb activities (Mhanna et al, 2016), leading to a more restrictive carpal tunnel and abnormal compression of the median nerve. Indeed, it has been shown that carpal tunnel syndrome is associated with TCL hypertrophy (John et al, 1983;Marquardt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mechanobiological responses due to repetitive muscle-ligament interaction could alter the material properties of the ligament (Magnusson, Narici, Maganaris, & Kjaer, 2008;Woo, Gomez, Woo, & Akeson, 1982), leading to increases in TCL thickness and stiffness (Mhanna, Marquardt, & Li, 2016). Changes to the TCL's material properties have been suggested as a possible etiology for CTS (John, Nau, Nahser, Reinhardt, & Venjakob, 1983;Marquardt, Gabra, Evans, Seitz, & Li, 2016). Finally, transecting the TCL as a surgical treatment for carpal tunnel syndrome unavoidably disrupts the muscle-ligament structure and function, which may explain postoperative complications such as weakened grip strength (Brooks, Schiller, Allen, & Akelman, 2003;Fuss & Wagner, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of TCL stiffness adaptation (Marquardt et al, 2016) and released carpal tunnel by TCL dissection (Kim et al, 2013) suggest that the change in TCL mechanical property might affect the compliance of carpal tunnel potentially contributing or alleviating median nerve compression. The TCL mechanical property manipulation could also be achieved by injecting collagenase reducing ligament stiffness by over 50% after 3-hour treatment (Prantil et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical environment of the carpal tunnel is the main determinant for compression neuropathy of the median nerve. Increases in tissue thickness and stiffness of the TCL have been shown in patients with carpal tunnel syndrome (Miyamoto et al 2013; Marquardt et al, 2016), suggesting the etiological mechanisms of the neuropathy. The mechanical role of the TCL in median nerve compression is also illustrated by carpal tunnel release surgery, in which the TCL is transected to reduce the mechanical constraint of the carpal tunnel as a means of nerve decompression.…”
Section: Introductionmentioning
confidence: 99%